EFFECTS OF SUPPLEMENTATION, DIET AND FASTING ON INSULIN RESISTANCE - Karolina Bieńkowska; Magdalena Rosiewicz; Anita Janda; Sylwia Bartolik; Marcin Durowicz; Iwona Górnicka; Aleksandra Pastuszek (International Journal of Innovative Technologies in Social Science, 2025)
Insulin resistance is a condition in which the decreased tissue sensitivity to insulin, which consequently leads to impaired glucose metabolism. This condition is the starting point for many chronic diseases, primarily type 2 diabetes, metabolic syndrome, PCOS, NAFLD and cardiovascular disease. This paper discusses the current state of knowledge on the effects of supplementation, diet and intermittent fasting on improving insulin sensitivity. The pathophysiological mechanisms of insulin resistance, diagnostic methods (including HOMA-IR, OGTT, metabolic clamp method), and its impact on the development and course of chronic diseases are presented.Special attention was given to supplements such as vitamin D, magnesium, zinc, Myo-inositol and omega-3 fatty acids, which through a variety of mechanisms can support glucose metabolism and improve insulin action. Also discussed was the role of caloric restriction and intermittent fasting, which have positive effects on body weight, metabolic profile and, most importantly, insulin sensitivity.The aim of the study was to highlight the importance of lifestyle modification and dietary interventions in the prevention and treatment of insulin resistance and its consequences. Due to the increasing prevalence of these disease entities in the general population, including among increasingly younger patients, it is necessary to implement appropriate preventive and therapeutic strategies in daily clinical practice.